On the Problem of Teaching Listening to Authentic Foreign Texts: Using Social Media - N. Kh. Sharipova; N. A. Kakhkhorova (International Journal on Orange Technologies, 2022)
The work is devoted to the problem of the formation of students' listening skills through the use of English-language materials of social networks. The relevance of the study is explained by the increasing role of social networks as a phenomenon of modern life. The purpose of the study is to study the principles of selecting social media materials that are appropriate to use in the process of teaching listening to high school students, and in testing these materials. The main tasks are to study the possibilities of using social networks in teaching listening and to develop types of tasks aimed at the formation of listening skills. The novelty of the research lies in the use of authentic English-language materials of the "In the contacts” social network for teaching listening. The developed tasks can be effectively used in teaching listening to students of schools and universities.